An investigation of the type and frequency of movement patterns of National Hockey League goaltenders - Bell, G. J.; Snydmiller, G. D.; Game, A. B. (International Journal of Sports Physiology and Performance, 2008)
Twenty-four National Hockey League (NHL) goaltenders were observed to determine the types and frequency of their movements during actual games. A secondary purpose was to compare these movements across the 3 periods of game play and between 2 NHL seasons (2003-04 and 2005-06) as a result of several rule changes between seasons. The mean (± SD) age, height, body mass, and years of NHL experience of the goaltenders were 30 ± 4 y, 85.4 ± 4.4 kg, 184.0 ± 3.8 cm, 6.6 ± 4.0 y, respectively. The mean (± SD) number of times and type of movements used during a game in order of most frequent were vertical movement (43.7 ± 10.3), moving laterally (39.7 ± 12.7), moving into full-butterfly position (32.1), anterior-posterior movement in front of goal crease (31.5 ± 11.5), skating out of the goal area to play the puck (19.7 ± 6.3), and using a half butterfly on a single leg pad (left = 5.2 ± 1.9, right = 6.4 ± 2.1). Goaltenders played the puck less frequently during the final period of the game than during the first 2 periods and more frequently between the 2 different NHL seasons after certain rule changes. It was concluded that NHL goaltenders move most frequently vertically, laterally, and out of the net to play the puck. In addition, goaltenders moved out of the goal area to play the puck less often in the third period but more frequently after several league rule changes designed to reduce this movement.